1995
DOI: 10.1021/ma00130a013
|View full text |Cite
|
Sign up to set email alerts
|

Dramatic Stabilization of a Hexagonal Columnar Mesophase Generated from Supramolecular and Macromolecular Columns by the Semifluorination of the Alkyl Groups of Their Tapered Building Blocks

Abstract: The tapered building blocks 3,4,5-tris[(4-(n.-decan-l-yloxy)benzyl)oxy]benzoic acid (8-10/0), 3,4,5-tris[(4-((

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
85
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(87 citation statements)
references
References 1 publication
2
85
0
Order By: Relevance
“…Some of the early investigations showed that rod-like liquid crystals with perfluorinated side chains, comparing to the ones with only alkyl side chains, through the "fluorophilic effects," are stiffer, miscible, and exhibit superior properties: including smectic layer assembling enhancements, high clearing points, broad mesomorphic temperature ranges, and so on (8). As a result, the fluorinated alkyl chains had recently been applied in DLCs with the hopes of improving their liquid crystal properties (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%
“…Some of the early investigations showed that rod-like liquid crystals with perfluorinated side chains, comparing to the ones with only alkyl side chains, through the "fluorophilic effects," are stiffer, miscible, and exhibit superior properties: including smectic layer assembling enhancements, high clearing points, broad mesomorphic temperature ranges, and so on (8). As a result, the fluorinated alkyl chains had recently been applied in DLCs with the hopes of improving their liquid crystal properties (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%
“…The association between these two polymers opens the way to various industrial applications. In addition, owing to the fluorophobic effect, the self‐assembly of semifluorinated compounds can be induced into supramolecular architectures9–20 such as liquid crystals and supramolecular soft matter, some of which may be suitable for electronic and optoelectronic applications.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of the structure of the ion‐pair of the ionic liquid on thermal and thermodynamic stability of the supramolecular dendrimers will be demonstrated with two AB 3 first generation dendrons, (3,4,5) 12G1‐CH 2 Y and (4‐3,4,5) 12G1‐CH 2 Y (where Y is the ionic liquid functionality attached to the apex of the dendron), three AB 2 second generation dendrons, (3,4‐3,5)12G2‐CH 2 Y , (4‐3,4‐3,5)12G2‐CH 2 Y , and (4‐3,4,5‐3,5)12G2‐CH 2 Y , and with an AB 2 third generation dendron, (3,4‐3,5‐3,5)12G3‐CH 2 Y . Both in the supramolecular columns and spheres the noncovalent interactions mediated by the ionic liquid provide a supramolecular polymer and, therefore, these assemblies represent dendronized supramolecular polymers 60–84…”
Section: Introductionmentioning
confidence: 99%